Diversidade e eficiência simbiótica de bactérias fixadoras de nitrogênio isoladas do quadrilátero ferrífero e capturadas por siratro (Macroptilium atropurpureum) e caupi (Vigna unguiculata) - Costa, Patrícia de Freitas (2016)
With the objective of evaluating the occurrence, genetic diversity, phenotypical diversity and symbiotic efficiency of nitrogen fixating Leguminosae nodulating bacteria (NFLNB) of five areas with different vegetation cover and soil characteristics, in the region of the Iron Quadrangle (Minas Gerais – Brazil), we collected soil from four sampling points in Canga, Cerrado, Forest, grass and eucalyptus areas. The access to NFLNB and the study on symbiotic efficiency was conducted in greenhouse using two leguminous plants: siratro (Macroptilium atropurpureum) and caupi (Vigna unguiculata). We obtained strains of NFLNB from all five evaluated areas. The caupi was more effective in the capture, since it captures strains from all points, in all areas, and presented the highest NFLBN density than siratro. The NFLNB community present in the grass area was more efficient than those from the other areas using siratro as bait plant, and the canga area presented lowest efficiency of the communities using caupi. A large number of strains obtained by both the caupi and siratro were efficient in the biological fixation of N2, revealing the biotechnological potential. The edaphic attributes pH, base saturation and content of aluminum were the most related to the biological attributes. Relative efficiency and shoot dry matter of the NFLBN communities were optimum indicators of the vegetation changes. For phenotypical diversity, we considered characteristics such as growth time, changes of pH of the culture medium, and size, shape and color of the colonies. Genetic characterization was obtained by means of partial sequencing of the 16S rRNA gene allied to the BOX-PCR technique. The forest and canga areas were more and less diverse, respectively. Some NFLBN genera such as Bradyrhizobium and Rhizobium, were captured only be the sitratro ou only by the caupi, demonstrating the importance of using more than one plant species in diversity studies. The present work is the main report on diversity and symbiotic efficiency of NFLBN strains in canga environment.